Penyembuhan Baby Blues Syndrome dan Post-Partum Depression Melalui Chandra Namaskara dan Brahmari Pranayama - Dewi, Ni Wayan Sri Prabawati Kusuma (Institut Hindu Dharma Negeri Denpasar, 2018)
Babies born through both normal and caesarean (sc) procedures, 50-80% make the mother face the risk of baby blues syndrome and post-partum depression. Baby blues syndrome, occurs in the first 2 weeks after giving birth, triggered by physical changes such asÂ swelling of the breast, pain in the area around the birth canal and uterus, changes in muscle tone, physical and mental fatigue that the mother feels. While post-partum depression lasts several months to many years later, this syndrome begins with a psychiatric disorder suffered by the mother before pregnancy, psychosocial stress, inadequate social support, and premenstrual dysphoric disorder. For that, this condition needs to be addressed immediately, through the healing techniques of Chandra namaskara and Brahmari Pranayama. Chandra namaskara arouses the feminine energy, the lunar energy in the motherâ€™s body, keeping the cerebral circulation fresh so that the sympathetic nerve activity diminishes. The effect of massage on the organs in the abdomen, increase peristaltic activity in the intestine, the lateral wall of the heart stretched perfectly so that no ischaemia occurs. Alteration of arthritis of the spinal joint can be removed by stretching the spinal muscles and ligaments between the vertebral bones through this series of asanas. While brahmari pranayama stimulates the brain part of the hypothalamus to activate the adrenal cortex system by sending signals to the pituitary gland so as not to secrete adrenocorticotropin (ACTH), so that ACTH, which had previously stimulated the outer layer of the adrenal glands (the adrenal cortex) to release a group of hormones (cortisol) did not secrete cortisol, but instead produced by the brain is actually the endhorpine that works for the bodyâ€™s immune, regulate emotions, relax of the body and be able to eliminate depression.